Indocyanine-green-mediated photothrombosis (IMP) with intravitreal triamcinolone acetonide for macular edema secondary to group 2A idiopathic parafoveal telangiectasis without choroidal neovascularization: A pilot study (2007)
Background: The purpose of this study was to determine the feasibility, safety and clinical effect of indocyanine green (ICG)-mediated photothrombosis (IMP) combined with intravitreal triamcinolone acetonide (IVTA) in patients with macular edema secondary to idiopathic parafoveal telangiectasis (IPFT) group 2A without choroidal neovascularization (CNV). Methods: Nine eyes of six patients that were treated with IMP immediately followed by IVTA at a dose of 4 mg participated in the study. Patients had a mean follow-up of 23.3 months (range 12-36 months). Patients underwent one or two sessions of IMP combined with IVTA ('study group'). An IVTA-only group of 19 eyes from 14 patients with macular edema secondary to IPFT group 2A that underwent an IVTA 4 mg without IMP ('IVTA-only group') was included for comparison. In addition, a matched control group of 40 eyes from 20 patients selected retrospectively from our medical records with macular edema secondary to IPFT group 2A without any therapy was included ('observation group'). Results: The best-corrected visual acuity (BCVA) remained stable in five eyes (55.5%). Four eyes (44.4%) demonstrated improvement of BCVA (? two ETDRS lines), and no eyes experienced worsening of visual acuity (? two ETDRS lines). A significant decrease in hyperfluorescence was not seen with fluorescein angiography (FA), however optical coherence tomography (OCT) showed a decrease in the size of inner intraretinal hyporeflective spaces or cystic edema. Two (22.2%) eyes developed an increase in intraocular pressure. However, it was medically controlled with topical anti-glaucoma medications. Cataract developed in five eyes (55.5%). Six of nine eyes (66.6%) required one retreatment during the study period. At the last follow-up (mean 21.1 months, range 12-30 months) in the IVTA-only group, 5 (25.3%) eyes improved BCVA, 11 (57.9%) eyes remained within two lines of baseline BCVA and 3 (15.8%) eyes lost BCVA. In the observation group, with similar follow-up, 87.5% of eyes showed either stabilization or deterioration of BCVA over time. Conclusions: Combined IMP and IVTA may provide stability or improvementin BCVA and fundus findings in eyes with macular edema secondary to IPFT group 2A without CNV at a minimum follow-up of 12 months. © Springer-Verlag 2007.